THE INTEGRATION OF PRAGMATISM IN ISLAMIC EDUCATION: RELEVANCE TO MODERN LEARNING - Suswati; Mahsun; Moh. Khoirul Fatihin (CV. Fahr Publishing, 2024)
Islamic education faces significant challenges in adapting to the evolving demands of modern society. One philosophical approach that offers a solution is pragmatism, which emphasizes experience, flexibility, and relevance in learning. This study aims to analyze the integration of pragmatism in Islamic education and its significance to modern learning. The research employs a qualitative method with a library research approach, examining academic literature related to educational philosophy and pragmatist theory. The findings indicate that applying pragmatism in Islamic education enhances learning effectiveness by emphasizing real-world experiences, curriculum flexibility, and the development of critical thinking and problem-solving skills. This approach enables students to understand Islamic teachings in a more practical and contextualized manner, preparing them to face contemporary challenges. Additionally, integrating technology in pragmatism-based learning further strengthens the relevance of Islamic education in the digital era. Therefore, more adaptive policies are needed to implement pragmatist principles in Islamic educational institutions to ensure sustainable and effective learning outcomes.